How to improve our understanding of solar wind-magnetosphere interactions on the basis of the statistical evaluation of the energy budget in the magnetosheath? - Vörös, Zoltán; Roberts, Owen W.; Yordanova, Emiliya; Sorriso-Valvo, Luca; Nakamura, Rumi; Narita, Yasuhito; Schmid, Daniel; Plaschke, Ferdinand; Kis, Árpád (Frontiers in Astronomy and Space Sciences, 2023)
Solar wind (SW) quantities, referred to as coupling parameters (CPs), are often used in statistical studies devoted to the analysis of SW–magnetosphere–ionosphere couplings. Here, the CPs and their limitations in describing the magnetospheric response are reviewed. We argue that a better understanding of SW magnetospheric interactions could be achieved through estimations of the energy budget in the magnetosheath (MS), which is the interface region between the SW and magnetosphere. The energy budget involves the energy transfer between scales, energy transport between locations, and energy conversions between electromagnetic, kinetic, and thermal energy channels. To achieve consistency with the known multi-scale complexity in the MS, the energy terms have to be complemented with kinetic measures describing some aspects of ion–electron scale physics.